EXPLORING THE ANTHELMINTIC POTENTIAL OF AZADIRACHTA INDICA AND ANDROGRAPHIS PANICULATA EXTRACTS AND THEIR SYNERGISTIC EFFECTS - Ramesh Kumari Dasgupta; Aniruddha Das; Rahul Maiti; Sajid Mondal (The Bioscan, 2025)
Helminth infections represent a significant global health concern, particularly in developing nations, contributing to malnutrition and other ailments. The rise of resistance to synthetic anthelmintics underscores the urgent need for alternative treatment strategies. This study investigated the phytochemical composition and anthelmintic efficacy of crude extracts from Azadirachta indica (AI) and Andrographis paniculata (AP), both individually and in combination, against helminths, with Albendazole serving as the standard reference. Anthelmintic activity, assessed by the time taken for paralysis and death of helminths, demonstrated a dose-dependent effect for all extracts (50, 75, and 100 mg/ml).Albendazole exhibited the most rapid action, inducing paralysis and death at 13±0.5 min and 22±0.4 min respectively, at 100 mg/ml. A. indica extract showed anthelmintic properties, with paralysis at 37±0.6 min and death at 50±0.3 min at 100 mg/ml. A. paniculata extract was more potent than AI, causing paralysis at 24±0.1 min and death at 27±0.1 min at the same concentration. Notably, the combined extract of AI and AP displayed a synergistic or additive effect, significantly enhancing anthelmintic activity. At 100 mg/ml, the combination induced paralysis in 19±0.4 min and death in 21±0.8 min, comparable to Albendazole's efficacy (paralysis at 75 mg/ml: 17±0.9 min; death at 100 mg/ml: 22±0.4 min). These findings suggest that the polyherbal combination of A. indica and A. paniculata is a promising candidate for a viable alternative or complementary therapy for helminth infections, potentially mitigating drug resistance.